THE LEADERSHIP MANAGEMENT OF SCHOOL PRINCIPALS IN IMPROVING SPIRITUAL INTELLIGENCE OF STUDENTS AT SMK YP-PGRI I MAKASSAR - Hermansyah Hermansyah; Muljono Damopolii; Sitti Syamsudduha (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to explain the description of the principal's leadership management in improving the spiritual intelligence of students at SMK YP-PGRI I Makassar and to explain the impact of the principal's leadership management in improving the spiritual intelligence of students at SMK YP-PGRI I Makassar. The type of research used in this research is qualitative. The results showed that the principal was able to manage all school resources, including Educators, Education Personnel, Students, infrastructure, finance, administration, planning of learning programs, programs of religious activities (spiritual activities), and others. other. Planning of school learning programs through structured scheduling by the Deputy Head of Curriculum with the involvement of the Principal and Educators in the preparation. The Principal of SMK YP-PGRI I Makassar seeks to organize educators and education staff through the division of tasks to each educator and education staff based on their potential and educational background, namely the distribution of task decrees in the hope that educators and education staff can work according to their job descriptions each.